Translation and validation of the Utian Quality of Life Scale in Serbian peri- and postmenopausal women. Issue 9 (September 2015) - Dotlic, Jelena; Gazibara, Tatjana; Rancic, Biljana; Radovanovic, Sanja; Milosevic, Branislav; Kurtagic, Ilma; Nurkovic, Selmina; Kovacevic, Nikolina; Utian, Wulf
Abstract: Objective: This study aimed to translate the Utian Quality of Life Scale (UQOL) into the Serbian and to assess its validity and psychometric properties in Serbian peri- and postmenopausal women. Methods: This survey included 200 perimenopausal and postmenopausal women. Women were approached after their regular gynecological checkup in two community health centers (city center and outskirts) in the capital city Belgrade. The following instruments were used: general questionnaire (sociodemographics, habits, and medical history), UQOL, Short Form-36, and Beck Depression Inventory. The UQOL was translated according to the recommended methodology for translating questionnaires, and its psychometric properties (internal consistency, factor analysis, discriminant validity, construct validity, and criterion validity) were tested. Results: The mean (SD) UQOL total score was 80.5 (13.5). The Cronbach's α coefficient for the entire scale was 0.83 (Occupational, α = 0.76; Health-Related, α = 0.72; Emotional, α = 0.36; Sexual, α = 0.66). All corrected item–total correlation coefficients were greater than 0.40, confirming that all items were appropriate parts of the UQOL. On exploratory factor analysis, we obtained six factors (five items formed two new clusters: Physical Fitness and Professional Recognition) that explained 85.7% of the total variance. The UQOL total score was significantly negatively correlated with Beck Depression Inventory score ( P = 0.001) and significantly positively correlated with all Short Form-36 domains ( P = 0.001). In addition, significant intercorrelations of UQOL domains also indicated good criterion validity. Conclusions: The Serbian version of the UQOL demonstrates satisfactory reliability and validity in the assessment of quality of life among peri- and postmenopausal women. The Serbian version of the UQOL is an adequate quality-of-life instrument in the Serbian language that can be applied in the everyday clinical setting.